Velocity Control for Coning Motion Missile System Using Direct Discretization Method - Rui-sheng Sun; Chao Ming (Discrete Dynamics in Nature and Society)
This paper presents a new coning motion control methodology, which takes into account the terminal speed constraint to design the velocity control system for a missile. By using a direct discretization method to transform the optimal control problem into a nonlinear dynamic programming problem, the optimal trajectory and velocity profile are obtained to satisfy the design index requirement. In order to perform the velocity control, a virtual moving target is proposed for the missile to chase along the optimized trajectory. Consequently, after building velocity control model, a velocity control law and control parameters of the coning motion are completed through the dynamic inversion theory. The simulation results suggest that the proposed control law has a good performance and could be applied to the guidance for the missile with terminal speed control constraint.